Acute Stroke Care and Thrombolytic Therapy Use in a Tertiary Care Center in Lebanon - Mazen J. El Sayed; Tharwat El Zahran; Hani Tamim (Emergency Medicine International)
Background. Thrombolytic therapy (rt-PA) is approved for ischemic stroke presenting within 4.5 hours of symptoms onset. The rate of utilization of rt-PA is not well described in developing countries. Objectives. Our study examined patient characteristics and outcomes in addition to barriers to rt-PA utilization in a tertiary care center in Beirut, Lebanon. Methods. A retrospective chart review of all adult patients admitted to the emergency department during a one-year period (June 1st, 2009, to June 1st, 2010) with a final discharge diagnosis of ischemic stroke was completed. Descriptive analysis was done followed by a comparison of two groups (IV rt-PA and no IV rt-PA). Results. During the study period, 87 patients met the inclusion criteria and thus were included in the study. The mean age was found to be 71.9 years (SD = 11.8). Most patients arrived by private transport (85.1%). Weakness and loss of speech were the most common presenting signs (56.3%). Thirty-three patients (37.9%) presented within 4.5 hours of symptom onset. Nine patients (10.3%, 95% CI (5.5–18.5)) received rt-PA. The two groups (rt-PA versus non rt-PA) had similar outcomes (mortality, symptomatic intracerebral hemorrhage, modified Rankin scale scores, and residual deficit at hospital discharge). Conclusion. In our setting, rt-PA utilization was higher than expected. Delayed presentation was the main barrier to rt-PA administration. Public education regarding stroke is needed to decrease time from symptoms onset to ED presentation and potentially improve outcomes further.